How AI will change the job of librarians: Galala University case study - Mohamed Sayed (Cybrarians Journal)
Artificial intelligence has become a significant role in the field of libraries and information because it is now thought to overlap with all scientific fields and has had a significant impact on journal development. This has led to a significant change in the role of library and information specialists. It is imperative that experts who are well-versed in and significant to them in that research introduce new services. A case study on the condition of the central library at GALALA University, the change in services, and the function of library specialists as a resource for information will be given along with the role that artificial intelligence plays in the field of library and information specialists. because of the sophistication and progress of the services provided in those services.